Vaginal histological changes after using intravaginal sponges for oestrous synchronization in anoestrous ewes - Manes, Jorgelina; Campero, Carlos Manuel; Hozbor, Federico Andres; Alberio, Ricardo; Ungerfeld, Rodolfo (Wiley, 2019)
To characterize the histological and cytological vaginal changes generated by the use of intravaginal sponge (IS) applied in oestrous synchronization treatments in ewes during mid‐non‐breeding season. Thirty‐five multiparous ewes were allocated to three experimental groups according to the moment in which the samples were taken: (i) ewes treated with IS containing 60 mg of medroxyprogesterone acetate for 14 days, sampled the day of IS removal (group ISR; n = 10), (ii) or after sponge removal at time of oestrus or 72 h after removal (group AR; n = 14) and (iii) ewes without sponge treatment that were sampled at the day of IS removal of the other groups (group CG; n = 11). Vaginal biopsies and cytological samples were taken from the anterior vaginal fornix area. The vagina of the CG group had a stratified squamous epithelium with a moderate degree of cellular infiltration with lymphocytes and plasma cells in the lamina propia. Treated ewes (ISR and AR) had epithelial hyperplasia and hypertrophy. ISR ewes had haemorrhage and perivascular infiltrate and an increased number of epithelial cells, neutrophils, macrophages and erythrocytes at IS removal. The use of IS generated histological and cytological alterations in the vaginal wall when used for oestrous synchronization in anoestrous ewes.